Pertumbuhan Tanaman Tomat yang Dibudidayakan di Tanah Mineral dengan Perlakuan Ampas Teh dan Kotoran Sapi - Mila Lukmana; Muhammad Helmy Abdillah (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2022)
Tomato is a vegetable commodity that is needed on a large scale so its cultivation needs to be intensified. Tomato production is often constrained due to productivity and limited land, thereby reducing genetic potential and poor fertility. Therefore, intensification measures are needed in optimizing productivity and land limitations, especially the problem of urban farming. Tea dregs and cow dung become potential as well as alternatives in increasing soil fertility, especially for urban farmers who use urban land and yards for cultivation activities. This study aims to determine the effect of the application of a combination of tea dregs and cow dung at an efficient and effective dose on the increase in plant height, leaf surface area, root volume, dry weight of tomato plants. This research was conducted from February 2021 to June 2021 with a factorial randomized block design (RAK) with a BNJ 5% analysis model. The combination treatments used were tea dregs (A) and cow dung (S) with a dose level of A0 = 0 g/polybag; A1 = 10 g/ polybag; A2 = 20 g/ polybag; A3 = 30 g/ polybag; S0 = 0 g/ polybag; S1 = 29.7 g/ polybag; S2 = 44.5 g/ polybag; S3 = 74.2 g/polybag combined between types of materials and dose levels so that there are 16 factorial combinations that were repeated 3 times. The results of this study indicated that treatment of A1S3 was effective and efficient in increasing plant height gain, encouraging the formation of leaf surface area, increasing root growth, and producing tomato plant dry weight.